Cranberry Polyphenols and Prevention against Urinary Tract Infections: A Brief Review - Llano, Dolores González de; Moreno-Arribas, M. Victoria; Bartolomé, Begoña (Current Advances in Chemistry and Biochemistry Vol. 4, 2021)
Cranberry (Vaccinium macrocarpon) is a distinctive source of polyphenols as flavonoids and phenolic acids that has been described to display beneficial effects against urinary tract infections (UTIs), the second most common type of infections worldwide. UTIs can lead to significant morbidity, especially in healthy females due to high rates of recurrence and antibiotic resistance. Strategies and therapeutic alternatives to antibiotics for prophylaxis and treatment against UTIs are continuously being sought after. Different to cranberry, which have been widely recommended in traditional medicine for UTIs prophylaxis, probiotics have emerged as a new alternative to the use of antibiotics against these infections and are the subject of new research in this area. Besides uropathogenic Escherichia coli (UPEC), the most common bacteria causing uncomplicated UTIs, other etiological agents, such as Klebsiella pneumoniae or Gram-positive bacteria of Enterococcus and Staphylococcus genera, seem to be more widespread than previously appreciated. Considerable current effort is also devoted to the still-unraveled mechanisms that are behind the UTI-protective effects of cranberry, probiotics and their new combined formulations. All these current topics in the understanding of the protective effects of cranberry against UTIs are reviewed in this paper. Finally, pieces of evidence regarding treatment against UTIs with probiotics and their combinations with cranberry are too limited to draw any conclusions but they seem to indeed be a promising strategy for future treatments.